Peng Chen, Mayor of Peking, during the mass rally to support the Vietamese people against U.S. imperialist armed agression - Chien Tzu-chieh,
Peng Chen, Mayor of Peking, during the mass rally to support the Vietamese people against U.S. imperialist armed agression.